2022
DOI: 10.1039/d2sc03868d
|View full text |Cite
|
Sign up to set email alerts
|

Designing inorganically functionalized magic-size II–VI clusters and unraveling their surface states

Abstract: Surface engineering is a critical step in the functionalization of nanomaterials to improve their optical and electrochemical properties. However, this process remains a challenge in II-VI magic-size clusters (MSCs) due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Following the initial observation of (CdSe) 33 and (CdSe) 34 in 2004, intense research activity has focused on the study of synthetic pathways and related formation mechanisms. This field has expanded dramatically since (CdSe) 13 MSCs were synthesized and isolated in solid form by Buhro and co-workers. , In recent years, several stoichiometric MSCs have been isolated in discrete, single-size purity. , For example, Hyeon and co-workers recently reported the crystal structure of a semiconductor Cd 14 Se 13 cluster . It is worth noting that although five members of stoichiometric cadmium-based II–VI MSCs have already been prepared and isolated, ,, the synthesis of pure (CdS) 13 MSCs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial observation of (CdSe) 33 and (CdSe) 34 in 2004, intense research activity has focused on the study of synthetic pathways and related formation mechanisms. This field has expanded dramatically since (CdSe) 13 MSCs were synthesized and isolated in solid form by Buhro and co-workers. , In recent years, several stoichiometric MSCs have been isolated in discrete, single-size purity. , For example, Hyeon and co-workers recently reported the crystal structure of a semiconductor Cd 14 Se 13 cluster . It is worth noting that although five members of stoichiometric cadmium-based II–VI MSCs have already been prepared and isolated, ,, the synthesis of pure (CdS) 13 MSCs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) was considered as a promising tool in analytical fields due to its high sensitivity and simple and controllable operation. Among various ECL emitters, g-C 3 N 4 was widely used due to its nontoxicity and low cost. To enhance the ECL intensity, S 2 O 8 2– was often used as its cathodic co-reactant. However, excessive S 2 O 8 2– with strong oxidation may cause oxidative damage to biomolecules and interference with biological samples. In previous work, we found that the endogenic dissolved O 2 could act as a cathodic co-reactant of three-dimensional (3D) g-C 3 N 4 to enhance its ECL emission, which could solve the above problem, and had further advantages of good biocompatibility and simple operation .…”
Section: Introductionmentioning
confidence: 99%
“…While the core of a NC determines many of its characteristic photophysical properties, these properties are often highly sensitive to disruption by defects at the surface of the NC. It has been shown that undercoordinated surface anions are a predominant cause of sub-bandgap trap states that localize charges and dominate exciton recombination. Due to this effect of surface anions, many NC syntheses are performed with an excess of cation precursors to ensure a cation-rich surface. , In addition, capping ligands are typically incorporated on the nanomaterial surface, playing a multifaceted role of passivating dangling surface bonds, ensuring charge balance, and promoting particle stability (both chemical and colloidal). Given the critical impact these ligands have on preserving NC properties, they are a subject of significant and continued study in the field. Numerous classes of both organic and inorganic ligands are used to functionalize NC surfaces.…”
Section: Introductionmentioning
confidence: 99%